Wealth shocks and macroeconomic dynamics - Daniel Cooper; Karen Dynan (Federal Reserve Bank of Boston, 2013)
The effect of wealth on consumption is an issue of longstanding interest to economists. Analysts believe that fluctuations in household wealth have driven major swings in economic activity. This paper considers so-called wealth effects - the impact of changes in wealth on household consumption and the overall macroeconomy. There is an extensive existing literature on wealth effects, but there are also many unanswered issues and questions. This paper reviews the important issues regarding the role wealth plays in the macroeconomy and argues that there is a need for much more wealth effect research as well as better data sources for conducting such analysis.
Keywords: E21; 330; housing wealth; financial wealth; wealth effects; consumption; borrowing constraints; saving; household debt; deleveraging